PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS V SDN 3 TELUK RHU - Iskandar, Azmi; Antosa, Zariul; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the low learning outcomes of PKN students whose average grade is still at 69.36, while the final grade applied in grade V of SD Negeri 3 Teluk Rhu is 70. This research is a class action research (PTK) consisting of two cycles, carried out in even semester 2016/2017. Subjects of this study amounted to 21 people. From 21 students 10 people completed and 11 people have not completed. This study aims to improve the learning outcomes of students of grade V of SD Negeri 3 Teluk Rhu by applying STAD type cooperative learning model. STAD type cooperative learning model is a group heterogeneous learning model. Instrument of this research consists of learning device and instrument of data collecting in the form of observation sheet and test question. The study was conducted in March-April 2017. The data were analyzed using SPSS 16 including teacher activity data and student activity and improvement of student learning outcomes. Data analysis of teacher activity and student activity is based on observations made by the observer during the course of action. While the data analysis of student learning outcomes done after the implementation of daily test cycle I and cycle II. Based on the result of observation of teacher activity and student activity happened improvement as follows: teacher activity in cycle I only reach 70%, in cycle II increased to 95% while in activity of student in cycle I only 65%, in cycle II increased to 95%. Analysis of student learning result data showed improvement as follows, improvement of learning masculinity in cycle I 15 people, cycle II entire student complete. Increased completeness caused by the increase in the average score of student learning outcomes from 65.71 in the initial score increased to 80 in the final repetition cycle II. This shows that the application of STAD learning model can improve the learning outcomes of PKN students of grade V SD Negeri 3 Teluk Rhu.Keywords: STAD type cooperative model, PKN learning outcomes